KETIDAKPASTIAN LEMBAGA PENJAMIN SIMPANAN SEBAGAI PENANGGUNG DALAM PERJANJIAN ANTARA NASABAH DAN BANK - Siti Malikhatun Badriyah; R Suharto; Siti Mahmudah; Marjo Marjo (Refleksi Hukum: Jurnal Ilmu Hukum, 2019)
The function of the Indonesia Deposit Insurance Corporation (IDIC) is to guarantee a deposit of customers. The guarantee is significantly important for the main financial industries, such as a bank whose activity is to raise funds from the public and distribute the funds back to the public. As a consequence, public trust becomes the primary factor. In spite of the useful function of the IDIC, the public is still not familiar with the organization and they often question whether the status of the IDIC is a guarantee or insurance. This issue potentially creates a dispute between parties who are the bank and the customer. Hence, this research aims to discover evidence relating to the IDIC as the guarantor in the agreement between bank and customer. This research used a legal pluralism method that integrates juridical research, sociological research (living law) and philosophical research. The result of the research indicates the uncertainty of the status of the IDIC, whether it is a guarantee or insurance, whereas both statuses maintain different legal consequences. The uncertainty may lead to legal uncertainty and result in the disruption of the balance of both parties’ legal relationships.